Students’ Perceptions on Individual Reconstruction Phase of Reading to Learn: A Qualitative Study - ani, Listy (Advances in Social Sciences Research Journal, 2017)
Continuous and never-ending research is being done on the areas of the four skills of English, speaking, reading, writing, and listening. Teachers as well as researchers of English everywhere are trying to improve the quality and methods of teaching in the hope that learners of English will be helped improve their language skills. One of the areas explored continuously is writing. In this paper, I want to describe how Academic Writing students in Semester II, 2015-2016 Academic Year responded to the fifth and sixth stages of Reading to Learn, which are individual reconstruction and individual construction/ writing. Respondents are 10 students of Academic Writing E, at the English Department of Satya Wacana Christian University Salatiga, Central Java, Indonesia. Purposive sampling was used to find the respondents. They were selected based on the questionnaires they filled in, and 4 types of students were selected: introvert, extrovert, visual, and auditory. However, due to the limitation of time and space, only 10 students’ opinions were analyzed in this paper. There were 5 introvert and 6 extrovert students altogether. Data were mainly derived from the students’ journals submitted after they passed through a stage. Findings show that both introvert and extrovert students’ perceptions varied, not depending on their personality types. Most of the students liked working individually in doing writing tasks.